2011
DOI: 10.1186/1471-2350-12-8
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial DNA 4,977-bp deletion and its implication in copy number alteration in colorectal cancer

Abstract: BackgroundQualitative and quantitative changes in human mitochondrial DNA (mtDNA) have been implicated in various cancer types. A 4,977 bp deletion in the major arch of the mitochondrial genome is one of the most common mutations associated with a variety of human diseases and aging.MethodsWe conducted a comprehensive study on clinical features and mtDNA of 104 colorectal cancer patients in the Wenzhou area of China. In particular, using a quantitative real time PCR method, we analyzed the 4,977 bp deletion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
89
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 42 publications
1
89
3
1
Order By: Relevance
“…In contrast to previous observations [15,17], which are consistent with expectations of higher rates of mtDNA deletion at the late stages of the disease, we observed that the mtDNA 3,867-bp deletion was more likely to be present in younger transgenic mice, in accordance with the recent results of Chen et al [22]. However, compared to wild-type mice, transgenic mice in general demonstrated higher percentages of mtDNA copies with deletions, supporting the previous findings in healthy and affected MJD individuals [17].…”
Section: Discussioncontrasting
confidence: 56%
“…In contrast to previous observations [15,17], which are consistent with expectations of higher rates of mtDNA deletion at the late stages of the disease, we observed that the mtDNA 3,867-bp deletion was more likely to be present in younger transgenic mice, in accordance with the recent results of Chen et al [22]. However, compared to wild-type mice, transgenic mice in general demonstrated higher percentages of mtDNA copies with deletions, supporting the previous findings in healthy and affected MJD individuals [17].…”
Section: Discussioncontrasting
confidence: 56%
“…On the other hand, Afshan et al hypothesized that CNV of mtDNA depends on damage and can function as a biomarker of mitochondrial dysfunction in a particular tissue (18). Changes in the copy number of mtDNA have been reported in sporadic colorectal carcinogenesis (19)(20)(21); however, there are few reports on investigations of CNV related to colitis cancer development.…”
mentioning
confidence: 98%
“…Chen et al investigated the common deletion in tumour tissue and paired non-tumour areas from colorectal cancer patients in the Wenzhou area of China. They found that the common deletion was more likely to be present in patients of younger age (≤65 years) and its level decreased as the cancer stage advanced (Chen et al 2011). In the present study we found that 100% of non-malignant colon and rectal tissues carried the deletion, although it was found to be more prevalent in the rectum.…”
Section: Discussionmentioning
confidence: 95%